Problematika Perencanaan dan Pelaksanaan Dakwah Nahdatul Ulama: Prespektif Manajemen Dakwah - Kasia Yuliana Barutu; Zainal Arifin (Kartika: Jurnal Studi Keislaman, 2026)
This research analyzes the issues of da'wah planning at the Nahdlatul Ulama Branch Management (PRNU) in Pagar Pinang Village, Central Tapanuli. The background of the research is based on the disconnection between formal management regulations and practical implementation at the grassroots level. The objective of the research is to identify managerial obstacles and formulate strategic solutions to enhance organizational accountability. The methodology used is descriptive qualitative with Henri Fayol's administrative management approach, where primary data is collected thru participatory observation and in-depth interviews with key informants. The research findings conclude that the main problem stems from the disparity between strong cultural-ideological solidity and a weak formal governance system. Although the principles of unity and continuity are organically maintained thru local traditions, the absence of systematic administrative infrastructure and precise Budget Plans (RAB) causes the management of preaching to be reactive and incidental. This condition demands a transformation toward accountable professional management to ensure the long-term stability of the organization